The effect of the training method on developing motor balance and handstand skill in gymnastics (Journal of the College of Basic Education, 2022)
The effect of the training method on developing motor balance and handstand skill in gymnasticsTeaching methods and methods developed as a link between the proposed curriculum and the development of the learning process itself. The appropriate method of teaching is the magic wand with which the teacher can translate what is in the curriculum into an acquired educational position. The person who wants to choose the task of teaching physical education must familiarize himself with the new foundations and methods of teaching and follow what suits him, which makes the educational material a lively and interesting subject for students. And to identify the training method for the development of motor balance and the skill of handstand in gymnastics. The two researchers used the experimental method by designing two equal groups, the community and the research sample, as the research community was determined in a deliberate way from the students of the Department of Physical Education / College of Basic Education / Al-Mustansiriya University. The sample percentage is 50%. The two researchers divided the sample randomly into two control and experimental groups by drawing names by lottery, and for the purpose of ensuring a single initiation line for the two groups, the researchers resorted to using the T-Test law for independent and equal samples in the variables dependent on the research, and all the results appeared with no significance Significance in the motor balance and standing on the hands, and then they performed the equivalence procedure, then the pre-test was conducted, and an educational unit was designed in the training style, the unit time is 90 minutes, and then the post-test was conducted. Balance of movement and the skill of standing on the hands. The adopted method also has an effect on the dependent variables, but not to the same extent as the training method. The emergence of a discrepancy in the rates of development between the pre and post tests of the control and experimental groups in the ability (motor balance) in favor of the post tests. The emergence of a discrepancy in the rates of development between the post tests of the control and experimental groups in skills (handstand) and in favor of the experimental group. One of the most important recommendations is the necessity of adopting the training method to develop special physical and motor abilities to develop the skills of ground movements in gymnastics. Emphasis on teaching and teaching the motor abilities of the skills of ground movements and not neglecting any of them